Optimal conditions of in vitro mycelial growth of Lentinus strigosus, an edible mushroom isolated in the Brazilian Amazon - Vargas-isla, Ruby; Ishikawa, Noemia Kazue (Mycoscience, 2008)
The protocols of in vitro cultivation described in the literature for mushrooms are usually correlated with temperate climate habitat, but it is necessary to study protocols for species of tropical climates. In this article, we collected, isolated, and evaluated the conditions of in vitro mycelial growth of Lentinus strigosus and correlated these with the characteristics of its habitat. These results indicate, as optimal conditions of in vitro mycelial growth for L. strigosus, the use of 35°C for incubation, initial pH from 5 to 7, without illumination, Sabouraud dextrose agar medium, and agitation for culture in liquid medium. © 2008 The Mycological Society of Japan and Springer.
Keywords: Basidiomycota; Fungi; Lentinus; Lentinus Strigosus